(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2012)
This study examined the impact of the inclusion of chemistry in national examination (NE) as a high stakes testing on some aspects of teaching chemistry as well as psychodynamic aspects of learning of chemistry at senior secondary school level. Causal-comparative research design was employed for this study. To conduct the study two five-points Likert-type scales were developed and validated, i.e. the teacher teaching scale (TT-Scale) and psychodynamic aspects of student learning scale (PSLScale). Samples for this study were 110 chemistry teachers as well as 240 science stream students in province of West Java drawn with multi-stage cluster sampling procedure. Data analysis using t-test and ANCOVA were conducted to examine the significance of mean differences of: Teacher’s pedagogical actions before vs. after chemistry included in the NE; Psychodynamic aspects of students’ learning of 11th graders (weaker exposed by NE) vs. 12th graders (stronger exposed by NE). It was found that the high-stakes testing changes significantly in the followings: Content to be taught more focused on examination content, teaching processes become more student-centered, and problem solving exercises become more dominant in teaching. With regards to psychodynamic aspects of student learning, it was revealed that 12th grade students tend to have higher level in the followings: Attitudes toward learning, motivation to learn, self-efficacy, and independent learning. Yet, it was also indicated that the students developed inappropriate beliefs on effective learning. However, the effect of high-stake testing on student’s test anxiety was not evidenced. Penelitian ini menguji dampak dari masuknya kimia dalam ujian nasional (UN) sebagai pengujian berisiko tinggi pada beberapa aspek kimia pengajaran serta aspek psikodinamik belajar kimia di tingkat sekolah menengah atas. Kausal-komparatif desain penelitian digunakan untuk penelitian ini. Untuk melakukan studi dua lima-poin Likert-jenis skala yang dikembangkan dan divalidasi, yaitu skala mengajar guru (TT-Scale) dan aspek psikodinamik skala belajar siswa (PSL-Skala). Sampel dalam penelitian ini adalah guru kimia 110 serta 240 siswa jurusan IPA di provinsi Jawa Barat digambar dengan multi-stage cluster sampling prosedur. Analisis data menggunakan t-test dan ANCOVA dilakukan untuk menguji signifikansi perbedaan rata-rata: tindakan pedagogis Guru sebelum vs setelah kimia termasuk dalam UN, aspek psikodinamik belajar siswa kelas 11 (lemah terpapar oleh UN) vs 12 grader (kuat terpapar oleh UN). Ditemukan bahwa perubahan pengujian berisiko tinggi secara signifikan pada berikut: Konten harus diajarkan lebih fokus pada konten pemeriksaan, proses mengajar menjadi lebih berpusat pada siswa, dan masalah latihan pemecahan menjadi lebih dominan dalam mengajar. Berkaitan dengan aspek psikodinamik belajar siswa, terungkap bahwa siswa kelas 12 cenderung memiliki tingkat yang lebih tinggi dalam berikut: Sikap terhadap belajar, motivasi belajar, self-efficacy, dan belajar mandiri. Namun, itu juga menunjukkan bahwa siswa mengembangkan kepercayaan yang tidak pantas pada pembelajaran yang efektif. Namun, efek dari tinggi-saham pengujian pada kecemasan tes siswa tidak dibuktikan.